(untitled) (World Science, 2019)
The primary purpose of this paper is to analyze the transformations in the international financial architecture and their impact on the national financial system. For this purpose, a multi-criteria analysis (matrix approach) is used, which represents a structured approach used to determine the general preferences between several alternative options, which lead to the achievement of several objectives. The approach of the matrix gives the possibility to combine the size of the set of the financial sector. The conclusions of this study consist in the fact that the complex resolution of the challenges in the international financial architecture implies the creation of foundations for the implementation of the progressive structural changes in the economy, capable of contributing to the sustainable economic development.